Postpartum women’s level of comprehension of newborn care instructions at a rooming-in facility - Dauber, Bruna Cabrera; Cunha, Maria Luzia Chollopetz da (Clinical and Biomedical Research, 2017)
Introduction: This study aimed to assess the postpartum women’s level of comprehension of newborn care practices taught at a rooming-in facility. Methods: In this cross-sectional study, a Likert scale was used to assess the participants’ level of comprehension of the postpartum instructions provided by the nursing staff at a maternity ward of a teaching hospital in southern Brazil. Results: A total of 196 women were interviewed. The analysis of the overall level of comprehension of newborn care instructions, assessed by means of Likert scale scores, was considered satisfactory, with a mean comprehension of 77.19% (SD: 17.3%) and a median comprehension of 80% (IQR: 70-90). Conclusion: The newborn care instructions provided by the nursing staff at a rooming-in facility were satisfactorily understood by the postpartum women. Keywords: Rooming-in; newborn; postpartum period; nursing care